Optimal Income Taxation with Asset Accumulation - Árpád Ábrahám; Sebastian Koehne; Nicola Pavoni (Center for Economic Studies and ifo Institute (CESifo), 2014)
Several frictions restrict the government's ability to tax assets. First, it is very costly to monitor trades on international asset markets. Second, agents can resort to nonobservable low-return assets such as cash, gold or foreign currencies if taxes on observable assets become too high. This paper shows that limitations in asset taxation have important consequences for the taxation of labor income. Using a dynamic moral hazard model of social insurance, we find that optimal labor income taxes become less progressive when governments face limitations in asset taxation. We evaluate the quantitative effect of imperfect asset taxation for two applications of our model.
Keywords: D82; D86; E21; H21; 330; optimal income taxation; capital taxation; progressivity